Principal's Leadership on “Sekolah Penggerak” Effectiveness in Improving the Quality of Education - Nafisah, Aisyah Durrotun; Antika, Dewi Hajar Windi; Latiana, Lita; Formen, Ali; Maronta, Yusuf (CV. Creative Tugu Pena, 2022)
The purpose of this study was to determine the effectiveness of